Analysis of the Effect of Additives on the Main Composition in Laboratory Conditions (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
Currently, there are possibilities for falsification of chocolate mass making, associated on the one hand with the replacement of raw materials, and on the other hand with a violation of technological processes in production. Therefore, it is necessary to improve the quality control system of incoming raw materials and the production technology.